Unmasking the pathways to workplace incivility: A mediated moderation model of despotic leadership, workload stress, and distributive justice in higher education - Muhammad Ahsan Ali; Haris Bin Khalid; Bilal Idrees; Zainab Naseer; Anum Sheraz (PLoS ONE, 2025)
The purpose of this study is to investigate how despotic leadership impacts workplace incivility through increased workload and to determine whether distributive justice moderates this relationship within selected higher education institutions in Rawalpindi and Islamabad. These two cities were specifically selected due to their significant representation of educational institutions, making them suitable samples for understanding dynamics within Pakistan’s higher education context. This study examines the relationship between despotic leadership (DL) and work place incivility (WPI) within the higher education sector of Rawalpindi and Islamabad. Specifically, it explores the mediating role of workload and the moderating role of distributive justice in this relationship. Grounded in the Conservation of Resources (COR) theory, this research extends existing literature by elucidating how resource depletion and accumulation shape employee behavior. A quantitative, cross-sectional survey-based methodology was utilized, collecting responses from 381 employees from higher education institutions located in Rawalpindi and Islamabad, with data analyses through IBM SPSS 27 and AMOS 22 using Confirmatory Factor Analysis (CFA), reliability tests, ANOVA, descriptive statistics, and correlation, and process macro direct effects, mediation, and moderation analyses to examine the proposed relationships. Indicates that despotic leadership significantly contributes to workplace incivility, primarily through increased workload. However, distributive justice serves as a mitigating factor, attenuating the adverse effects of workload on workplace incivility. The results confirm the mediating role of workload and the negative moderating influence of distributive justice. These insights underscore the necessity for organizational leadership to adopt more equitable and ethical management practices. Additionally, human resource policies should emphasize fairness and actively address complaints related to unfair treatment. The study posits that maintaining fairness in workload distribution, enhancing hiring practices to deter the emergence of despotic leaders, and establishing secure mechanisms for reporting grievances are critical steps for organizations seeking to curb workplace incivility. It underscores the centrality of distributive justice in mitigating negative interpersonal dynamics and fostering a more positive organizational climate. Moreover, initiatives such as impartial investigations and civility training programs are identified as pivotal in strengthening workplace relationships and preventing the escalation of retaliatory behaviours that contribute to a spiraling effect of incivility. Our study is limited by its focus on higher education institutions in Islamabad and Rawalpindi, suggesting the need for future research across broader sectors, cities, and global contexts. This research extends prior work in organisational behaviour and leadership studies, particularly by building upon the Conservation of Resources (COR) theory and the workplace incivility literature. It empirically examines the effect of despotic leadership on workplace incivility, highlighting workload as a mediating mechanism and distributive justice as a moderating force. By focusing on the higher education context, the study addresses a significant gap, providing a nuanced understanding of how leadership dynamics and perceptions of fairness jointly influence patterns of incivility through a mediated moderation framework.